Wacana Melegalkan LGBT di Indonesia (Studi Analisis LGBT dalam Perspektif Ham dan Pancasila) - Miskari Miskari (Raheema, 2016)
Lesbian, gay, bisexual and transgender phenomenon is one of the alternative lifestyle that spreads in Indonesia which is experienced by teenagers. It creates new problem for teenagers, their family, and their surroundings. The biggest problem in this case is there’s no specific step for counselor and psychiatrist to help transgender, gay, or lesbian counselee. This article deals with the new issue of homosexuality from the perspective of human rights international law (HAM) and Pancasila. The result of understanding towards human rights international law as well as towards Indonesia law (Pancasila) as the blessings for the universe places human beings in the most respected position. However there emerge the phenomenon of non-mainstream sexual orientation, such as lesbian, gay, bisexual and transgender (LGBT) which is believed part of propaganda of human rights. The fundamental principle of the concept of state law is rule by law is not rule by man, which means that the law was intended implies enforcement of recognition, equality, individual freedom, and human rights. But in Indonesia has the concept of a state of law that has the characteristics of Pancasila, because Pancasila is Staats fundamental norm for Indonesia, so that the implementation of the concept of state of law in Indonesia should be underlying by moral principle from precepts of the Pancasila, and therefore the author tried to look at the characteristics of the concept of state law Pancasila. Even if these laws are loosely enforced, their mere existence translates into legal and societal stigmatization by branding LGBT people as immoral. In essence, Indonesia need to present frontline in keep identity his people and do not terikut current globalization who break the identity of we, then the it must be remembered our country legal state and also crusader for human rights was one understand liberalism being without batas.oleh therefore, let us back at the identity of, back to of philosophy pancasila and the constitution of 1945 by means of infuse religious values and culture sublime. then, Pancasila wiil reject LGBT